RETROSPECTIVE ANALYSIS OF BORDERLINE OVARIAN TUMORS: OUTCOMES AT A SINGLE CENTER - ŞAHİN, NURHAN; YILMAZ, ERCAN; Sahin, NURHAN; KÖLELİ, IŞIL; MELEKOĞLU, RAUF; Tanrikut, Emrullah; Faydali, Simge; KARAER, ABDULLAH; Coskun, Ebru Inci (My University, 2019)
We wanted to discuss our experiences in the approach to borderline ovarian tumors, which constitute a group different from epithelial ovarian tumors with respect to their biological structure in line with retrospective information gathered from our cases. A total of 25 patients operated on for the indication of adnexal masses diagnosed as borderline ovarian tumors based on frozen section results were included in our study. Patient age, tumor diameter, tumor markers and surgeries performed were discussed in the light of the literature. Statistical analyses were performed using the SPSS software. The patient mean age was 43.84 +/- 11.34 years. The mass was localized in the right (n=13), left (n=11) or both (n=1) adnexal regions. The mean tumor diameter was 12.9 +/- 5.84 cm. Histopathologic examination established the diagnosis of serous borderline (n=14 patients) and mucinous borderline (n=11) ovarian tumors. Although the results of our study are consistent with current literature data, a greater number of current studies should be performed on borderline ovarian tumors, which are defined as a class of tumors different from epithelial ovarian tumors.